miR-125b-1 is repressed by histone modifications in breast cancer cell lines - Cisneros-Soberanis, Fernanda (Springerplus, 2016)
PURPOSE: Downregulation of miR-125b-1 is associated with poor prognosis in breast cancer patients. In this work we investigated the effect of histone modifications on the regulation of this gene promoter. METHODS AND RESULTS: We evaluated the enrichment of two histone modifications involved in gene repression, H3K9me3 and H3K27me3, on the miR-125b-1 promoter in two breast cancer cell lines, MCF7 (luminal A subtype) and MDA-MB-231 (triple-negative subtype), compared to the non-transformed breast cell line MCF10A. H3K27me3 and H3K9me3 were enriched in MCF7 and MDA-MB-231 cells, respectively. Next, we used an EZH2 inhibitor to examine the reactivation of miR-125b-1 in MCF7 cells and evaluated the transcriptional levels of pri-miR-125b-1 and mature miR-125b by qRT-PCR. pri-miRNA and mature miRNA transcripts were both increased after treatment of MCF7 cells with the EZH2 inhibitor, whereas no effect on miR-125b-1 expression levels was observed in MDA-MB-231 and MCF10A cells. We subsequently evaluated the effect of miR-125b-1 reactivation on the expression and protein levels of BAK1, a target of miR-125b. We observed 60 and 70 % decreases in the expression and protein levels of BAK1, respectively, compared to cells that were not treated with the EZH2 inhibitor. We over-expressed KDM4B/JMJD2B to reactivate this miRNA, resulting in a three-fold increase in miR-125b expression compared with the same cell line without KDM4B/JMJD2B over-expression. CONCLUSION: The miR-125b-1 is repressed by different epigenetic mechanisms depending on the breast cancer subtype and that miR-125b-1 reactivation specifically eliminates the effect of repressive histone modifications on the expression of an pro-apoptotic target. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s40064-016-2475-z) contains supplementary material, which is available to authorized users.